Measuring political dynasties in Metro Manila - Balanquit, Romeo T.; Coronel, Lianca O.; Yambao, Jose Y. (2017)
This paper aims to measure the intensity of political dynasties within the local governments of Metro Manila. Specifically, it tries to answer some questions: Which cities have the highest incidence of political dynasties? Do they necessarily exhibit low levels of political competition? Which families hold the highest intensity of political dynasty in the region? Using official local election results since 1988, we construct and apply a political dynasty index that provides a quantifiable and comparable measure of the prominence of different political families in different localities. We assign weights to family members holding local government positions to measure their horizontal and vertical linkages. Horizontal linkages refer to the relationships among family members holding different positions during a given political term, while vertical linkages refer to the ties among family members in office between two consecutive terms. The degree of entrenchment in power of a ruling family is measured by aggregating the values of its horizontal and vertical linkages.
Keywords: Public officers -- Corrupt practices; Politics and government; Political dynasties